Influence of Polysaccharides From Polygonatum kingianum on Short-Chain Fatty Acid Production and Quorum Sensing in Lactobacillus faecis - Yang, Min; Meng, Fanying; Gu, Wen; Fu, Lihui; Zhang, Fan; Li, Fengjiao; Tao, Yating; Zhang, Zhengyang; Wang, Xi; Yang, Xingxin; Li, Jingping; Yu, Jie (Frontiers in Microbiology, 2021)
Polysaccharide is one of the main active ingredients of Polygonatum kingianum, which has been proven to regulate the balance of gut microbiota. For the first time, this study focused on the regulation of polysaccharides from Polygonatum kingianum (PS) on Lactobacillus faecis, a specific probiotic in the intestinal tract. PS effectively promoted the biomass, biofilm and acetic acid production in L. faecis 2-84, and enhanced quorum sensing (QS) signaling. The characteristics of gene sequence were analyzed using genomics approaches, and L. faecis 2-84 was found to encode 18 genes that are closely related to QS and 10 genes related to short-chain fatty acids (SCFAs). Additionally, transcriptome and proteome analysis demonstrated that PS could promote the QS system of L. faecis by enhancing the transcription of oppA gene and expression of oppD protein. PS also regulated the production and metabolism of SCFAs of L. faecis by upregulating the expression of ldh and metE gene and adh2 protein, and downregulating the expression of mvK gene. In conclusion, it was speculated that PS could affect intestinal SCFAs production by affecting the QS system and SCFAs production in L. faecis. The present study implied that PS might have a role in promoting the growth of intestinal probiotics, where the QS system and SCFAs might be two of the important mechanisms for the probiotic activity of PS.